2019
DOI: 10.1097/iop.0000000000001557
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Large Upper Eyelid Defects With Bilobed Flap and Tarsoconjunctival Graft

Abstract: Purpose: To describe the reconstruction of large upper eyelid defects with bilobed flap and tarsoconjunctival graft. Methods: The medical records of 5 patients who underwent upper eyelid tumor excision and eyelid reconstruction with a bilobed flap were reviewed. Various parameters, including demographic and clinical data, defect diameter, primary defect closure, complications, and follow-up time, were recorded. After tumor excision, the posterior lamell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The most common is the Cutler-Beard procedure [6] , a two-step procedure where a full-thickness bridge flap raised from the lower eyelid is advanced to the upper eyelid defect, which will be divided after a few weeks. [7] The Cutler-Beard procedure has become the mainstay of large upper eyelid reconstruction. However, many have pointed to the lack of rigid support in the upper eyelid posterior lamella as one of its disadvantages, which causes entropion and ocular surface abrasions that can lead to eye irritation.…”
Section: Discussionmentioning
confidence: 99%
“…The most common is the Cutler-Beard procedure [6] , a two-step procedure where a full-thickness bridge flap raised from the lower eyelid is advanced to the upper eyelid defect, which will be divided after a few weeks. [7] The Cutler-Beard procedure has become the mainstay of large upper eyelid reconstruction. However, many have pointed to the lack of rigid support in the upper eyelid posterior lamella as one of its disadvantages, which causes entropion and ocular surface abrasions that can lead to eye irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies reported that a large defect of the upper eyelid was reconstructed by one-stage surgery using FTG transplantation. 22 , 23 Postoperative complications were observed in 40–60% of these reports, and Patrinely et al. 24 noted that reoperation was performed in about 35% of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, it still needs further validation by recruiting more patients and following up extended period. As for the reconstruction of sizeable upper eyelid defects, Yazici et al (22) reported a bilobed flap combined with a tarsoconjunctival graft from the contralateral upper eyelid. That was demonstrated to be a good alternative for the single-stage procedure for sizeable upper eyelid defects.…”
Section: Contralateral Tarsoconjunctival Graftmentioning
confidence: 99%